MEMPERSIAPKAN SISWA MERAIH PRESTASI DALAM KOMPETISI MATEMATIKA: APA YANG DILAKUKAN GURU? - Rustam Effendy Simamora; Zainuddin Suardi; Eka Widyawati (Mathematics Education And Application Journal (META), 2023)
This research aimed to describe the role undertaken by teachers at SMP Negeri 1 Tarakan, one of the public junior high schools in Tarakan, Indonesia, in preparing their students to succeed in mathematics competitions. This qualitative research employed a case study approach. The data collection techniques included interviews, documentation, and observation. The data analysis consisted of several interactive steps: preparing the collected data, reading it repeatedly to comprehend it, coding, identifying and testing themes through triangulation and member checking, describing the established themes, interpreting the themes and descriptions, and drawing conclusions. We also conducted peer debriefing during coding and writing research reports. Based on the data analysis, the findings regarding the role of teachers in preparing students for participation in mathematics competitions in the school consisted of two categories: students selection and coaching. Mathematics teachers select students through two main steps: set criteria and analyze students’ mathematical abilities. While coaching students to prepare for competition participation, teachers employed a personalized approach, facilitated student learning, motivated students, and utilized resources and facilities.Keywords: case study, mathematics competition, mathematics in junior high school, teacher roles. Penelitian ini bertujuan untuk mendeskripsikan hal yang dilakukan oleh guru di SMP Negeri 1 Tarakan dalam mempersiapkan siswanya untuk meraih prestasi dalam kompetisi Matematika. Jenis penelitian ini adalah kualitatif dengan pendekatan studi kasus. Adapun teknik pengumpulan data adalah wawancara, dokumentasi, dan observasi. Analisis data yang dilakukan terdiri dari beberapa langkah interaktif: mempersiapkan data yang telah terkumpul, membaca berulang-ulang untuk memahami semua data, melakukan pengkodean, menentukan tema dan mengujinya melalui triangulasi dan memeriksa anggota, mendeskripsikan tema yang sudah ditetapkan, menginterpretasi tema dan deskripsi tersebut, dan menarik kesimpulan. Sepanjang melakukan pengkodean dan penulisan laporan penelitian, kami juga melakukan peer debriefing. Berdasarkan hasil analisis data, temuan tentang bagaimana peran guru dalam mempersiapkan siswa untuk mengikuti kompetisi Matematika  di sekolah tersebut terdiri dari dua kategori: memilih siswa dan melakukan pembinaan. Guru Matematika memilih siswa dengan dua langkah utama, yaitu menetapkan syarat dan menganalisis kemampuan Matematika siswa. Selama membina siswa untuk mempersiapkan mereka mengikuti kompetisi, guru melakukan pendekatan personal, memfasilitasi siswa dalam belajar, memotivasi siswa, dan memanfaatkan sarana dan prasarana.Kata kunci: kompetisi Matematika, Matematika SMP, peran guru, studi kasus.